Prevalence of Antibiotic and Heavy Metal Resistance Determinants and Virulence-Related Genetic Elements in Plasmids of Staphylococcus aureus - Bukowski, Michal; Piwowarczyk, Rafal; Madry, Anna; Zagorski-Przybylo, Rafal; Hydzik, Marcin; Wladyka, Benedykt (Frontiers in Microbiology, 2019)
The use of antibiotics on a mass scale, particularly in farming, and their release into the environment has led to a rapid emergence of resistant bacteria. Once emerged, resistance determinants are spread by horizontal gene transfer among strains of the same as well as disparate bacterial species. Their accumulation in free-living as well as livestock and community-associated strains results in the widespread multiple-drug resistance among clinically relevant species posing an increasingly pressing problem in healthcare. One of these clinically relevant species is Staphylococcus aureus, a common cause of hospital and community outbreaks. Among the rich diversity of mobile genetic elements regularly occurring in S. aureus such as phages, pathogenicity islands and staphylococcal cassette chromosomes, plasmids are the major mean for dissemination of resistance determinants and virulence factors. Unfortunately, a vast number of whole genome sequencing projects does not aim for complete sequence determination, which results in a disproportionately low number of known complete plasmid sequences. To address this problem we determined complete plasmid sequences derived from 18 poultry S. aureus strains and analysed the prevalence of antibiotic and heavy metal resistance determinants, genes of virulence factors as well as genetic elements relevant for their maintenance. Some of the plasmids have been reported before and are being found in clinical isolates of strains typical for humans or human ones of livestock origin. This shows that livestock-associated staphylococci are a significant reservoir of resistance determinants and virulence factors. Nevertheless, nearly half of the plasmids were unknown to date. In this group we found a potentially mobilisable plasmid pPA3 being a unique example of accumulation of resistance determinants and virulence factors likely stabilised by a presence of a toxin-antitoxin system.